PLC-Controlled Coordination of Multi-Arm Robotics Without Cooperative Devices for Task Execution - Tiongson, Eisley John (Journal of Advanced Mechanical Engineering Applications, 2025)
The integration of multiple robotic arms for collaborative tasks often involves complex cooperative motion functions. This study introduces a research framework aimed at orchestrating multi-robotic arms for non-cooperative task execution in a slot-car transfer system, controlled solely by a Programmable Logic Controller (PLC). Unlike traditional approaches reliant on synchronized controllers, this framework excludes cooperative motion functions, focusing on two robot arms with six and four degrees of freedom. The PLC governs and coordinates the sequential movements of both arms, utilizing readily available laboratory and commercial components. To ensure compatibility and synchronization, a rigorous analysis of component specifications was conducted, addressing I/O signal mapping, voltage matching, and mechanical adaptation. A PLC-based control system manages coordination through pre-programmed delays, sensor feedback loops, and independent motion trajectories, ensuring precise and repeatable execution. Custom platform holders were developed to facilitate stable grasping and transfer of the slot car. This study specifically outlines the process of transferring a slot car across two platform tracks using Selective-Compliance Assembly Robot Arm (SCARA) and Articulated Robot Arm. Experimental results validate the feasibility and effectiveness of the proposed PLC-controlled coordination method, demonstrating that different robot arms can collaborate efficiently without requiring cooperative motion functions. The findings highlight a scalable and adaptable approach for integrating heterogeneous robotic systems in real-world industrial applications.